HUBUNGAN POWER OTOT TUNGKAI DAN KOORDINASI MATA-KAKI DENGAN AKURASI MELAKUKAN LONG PASSING PADA TIM SEPAKBOLA PS DABINK KECAMATAN TAMBANG KABUPATEN KAMPAR - Syaprizal Syaprizal; Slamet Slamet; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: In this research there were very problems with the lack of leg muscle and eye and foot coordination with the accuracy of the long passing of the PS Dabink soccer team, Tambang District, Kampar Regency. The purpose of this research was to determine and prove that there is a link between leg muscle power and eye-foot coordination on the accuracy of long-term transmission of PS Dabink football team, Tambang District, Kampar Regency. The type of investigation used is the type of correlation investigation, this investigation is a correlational investigation by comparing the results of measurements between different variables to find the level of the relationship between these variables. The population in this research was 14 people from the PS Dabink soccer team. The sample used in this research was 14 people. As Arikunto (2006: 134) has indicated that if the population size is less than 100, the entire population must be sampled to obtain representative data. The instruments used in this research are (a) Standing broad jump, (b) soccer wall volley test, and (c) Bobby Charlton gastric passage. Then the data test using the normality test, normality test data with liliefors test, correlation analysis. X1 L₀max variable normality test (0.1069) < Ltable (0.2270), X2 L₀max normality test variable (0.0950) < Ltable (0.2270) and Y variable normality test (0.2064) < Ltable (0, 2270). With this, the data is distributed normally and the conclusions of the study show that the hypothesis is accepted at a significant level α = 0.05, in other words, there is a connection between leg muscle strength and eye-foot coordination on the accuracy of the long-pass from the PS Dabink football team, Tambang Subdistrict, Kampar Regency with rcount (1,020) > table (0.553).Key Words: Leg Muscle, Ankle Coordination, Passing By, Football